Interaction Patterns of Students at the Cipasung Tasikmalaya Islamic Boarding School - Elis Solihat; Siti Komariah; Siti Nurbayani (Universitas Majalengka, 2023)
Pesantren as an educational institution is not only a place to transfer religious knowledge, but as a place for regeneration of formidable scholar and fighter. But currently there are many various cases of violence that occur in Islamic boarding school, both physical violence and sexual violence that occur against students, this is very ironic because the community’s interest in educating their children in pesantren is icreasing, giving rise to concerns. The purpose of this study is to provide an overview of the interactions carried out by students who choose to attend Islamic boarding schools, how they interact with their friends who have different backgrounds, different regional origins, also different characters and habits. This study uses a qualitative approach with interview techniques and is supported by literature studies, the researcher selects 6 students consisting 3 male students and 3 female students. The results of this study are forms of associative interaction that is built between students is tolerance that are established, when they are able to accept differences brought by fellow students, there is a feeling of sympathy that leads them to carry out a process of collaboration. Acculturation where the existing culture becomes a mixed culture from various regions, although dispute and conflict sometimes occur, this can be resolved by a process of accmodation interaction by prioritizing of advize to do good thing, and also mediation, this cannot be separated from the cultivation of tolerance values which are always sosialization by the the teacher or kyai in Islamic boarding schools.